Bessel Transform of -Bessel Lipschitz Functions - Radouan Daher; Mohamed El Hamma (Journal of Mathematics)
Using a generalized translation operator, we obtain an analog of Theorem 5.2 in Younis (1986) for the Bessel transform for functions satisfying the -Bessel Lipschitz condition in .